2021
DOI: 10.1212/nxi.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20 therapies and pregnancy in neuroimmunologic disorders

Abstract: ObjectiveTo report pregnancy outcomes and disease activity (DA) in women with MS, neuromyelitis optica spectrum disorders (NMOSDs), and other neuroimmunologic diseases (ONID) after treatment with rituximab (RTX)/ocrelizumab (OCR) 12 months before or during pregnancy.MethodsData were collected in the German MS and pregnancy registry and centers from the Neuromyelitis Optica Study Group. Sixty-eight known outcomes of 88 pregnancies from 81 women (64 MS, 10 NMOSD, and 7 ONID) were included and stratified in 3 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 37 publications
2
56
0
3
Order By: Relevance
“…These results suggest a prolonged protective effect on MS disease activity of rituximab, which can encompass pregnancy and postpartum period, without the high risk of disease reactivation or rebound described with natalizumab withdrawal before pregnancy (111). In line with these data, a German cohort study (112), analyzing 88 pregnancies from 81 women with neuroimmune diseases (including MS and NMOSDs) treated with anti-CD20 mAbs in the year before conception, showed a good control of disease activity during pregnancy and postpartum, with no major safety concerns (with the exception of two congenital abnormalities reported in women exposed to ocrelizumab during pregnancy) and with pregnancy outcomes within the range expected for the general population. An interesting case series about 11 pregnancies in 10 women (7 with MS and 3 with NMOSDs) treated with rituximab within 6 months of conception, seems to confirm these safety and efficacy findings: indeed, all completed pregnancies resulted in term live births of healthy newborns, no maternal relapses occurred before/during pregnancy and only one was observed in the post-partum (113).…”
Section: Special Populationsupporting
confidence: 69%
“…These results suggest a prolonged protective effect on MS disease activity of rituximab, which can encompass pregnancy and postpartum period, without the high risk of disease reactivation or rebound described with natalizumab withdrawal before pregnancy (111). In line with these data, a German cohort study (112), analyzing 88 pregnancies from 81 women with neuroimmune diseases (including MS and NMOSDs) treated with anti-CD20 mAbs in the year before conception, showed a good control of disease activity during pregnancy and postpartum, with no major safety concerns (with the exception of two congenital abnormalities reported in women exposed to ocrelizumab during pregnancy) and with pregnancy outcomes within the range expected for the general population. An interesting case series about 11 pregnancies in 10 women (7 with MS and 3 with NMOSDs) treated with rituximab within 6 months of conception, seems to confirm these safety and efficacy findings: indeed, all completed pregnancies resulted in term live births of healthy newborns, no maternal relapses occurred before/during pregnancy and only one was observed in the post-partum (113).…”
Section: Special Populationsupporting
confidence: 69%
“…In addition, it was demonstrated that a treatment with ocrelizumab or rituximab prior to conception might be an interesting option for women with RRMS or NMOSD for controlling disease activity during pregnancy and postpartum. 35 …”
Section: Resultsmentioning
confidence: 99%
“…Since then, data acquisition was improved and adapted and women with neuromyelitis optica spectrum disorders (NMOSD) 35 were included, as well as questionnaires to measure the Expanded Disability Status Scale (EDSS) 36 and developmental delays. 37 The follow-up period was also extended to up to 6 years for live births and up to 6 months for miscarriages.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, it was shown that PRA could be prevented without rituximab reinfusion during pregnancy in women with NMOSD treated with rituximab before pregnancy. To date, pregnancy outcomes in 16 patients with NMOSD treated with rituximab before pregnancy have been reported [31‐35]. Because the biological effect of B cell depletion can be maintained several months after elimination of the drug [36], rituximab can offer unique advantages preparing for pregnancy.…”
Section: Discussionmentioning
confidence: 99%